2019
DOI: 10.1101/697391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Theory of Minds: Managing mental state inferences in working memory is associated with the dorsomedial subsystem of the default network and social integration

Abstract: We often interact with multiple people at a time and consider their various points-of-view to facilitate smooth social interaction. Yet, how our brains track multiple mental states at once, and whether skill in this domain links to navigating real-world social interactions, remains underspecified. To fill this gap, we developed a novel social working memory paradigm in which participants manage two- or four-people’s mental states in working memory, as well as control trials in which they alphabetize two- or fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Our sample was heterogenous in terms of index trauma type, which increases generalizability but does not allow for close examination of whether trauma type, such as interpersonal versus noninterpersonal trauma, has particularly strong associations with SWM and social connection. As previously described (Meyer & Collier, 2020), while our calculation of task accuracy assumes that all relationship partners' mental states impact each other equally, relationship partners likely impact each other's mental states to different degrees, for example, as a function of the importance of the relationship or the frequency of contact.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our sample was heterogenous in terms of index trauma type, which increases generalizability but does not allow for close examination of whether trauma type, such as interpersonal versus noninterpersonal trauma, has particularly strong associations with SWM and social connection. As previously described (Meyer & Collier, 2020), while our calculation of task accuracy assumes that all relationship partners' mental states impact each other equally, relationship partners likely impact each other's mental states to different degrees, for example, as a function of the importance of the relationship or the frequency of contact.…”
Section: Discussionmentioning
confidence: 99%
“…Greater recruitment of the dorsomedial subsystem supports better SWM, which is in turn associated with better social skills and more social integration (Meyer & Collier, 2020; Meyer et al, 2012; Meyer, Taylor, et al, 2015). We found that individuals with PTSD exhibited hyperactivation within this subsystem, but also poorer accuracy on four‐load trials compared to trauma‐exposed controls—which we speculate may indicate that those with PTSD exert more cognitive effort when inferring others' mental states.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations